Dragqueenismo no Cariri cearense: tradição, corpo, cultura e performance - Martins, Enrique Bruno Lima (Universidade Federal de São Carlos, 2023)
This work intends to discuss about the practice of drag queenism in Cariri, which is located in the south region of Ceará and how the actors of this art are articulated in an inland region, contributing to the debate about the possibilities and forms provided by drag art. In addition to the interviews with drag queens from Cariri, the analyzes take place in two main moments, which took place in two bars in the region, one in the city of Crato and the other in Juazeiro do Norte, where, respectively, one takes place a competition of drag queens and in the other there was a drag show interpreting Madonna. It is not my intention to construct or elaborate any dimension that would be able to understand the drag phenomenon in its entirety, or try to measure the degree of subversion or assimilation that exists in this art. I propose here a sample of the critical possibilities that are offered by these subjects who, from the hinterland of Ceará, dispute through dragqueenism the affirmation of their artistic identities, contributing to the diffusion and affirmations of the regional culture.
Dragqueenism in Ceará's Cariri: tradition, body, culture and performance
Keywords: Dragqueenismo; Cultura; Tradição; Corpo; Dragqueenism; Culture; Tradition; Body; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS